1999
DOI: 10.1016/s0893-133x(98)00107-9
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Altered In Vivo Benzodiazepine Receptor Binding in Schizophrenia

Abstract: Deficits in gamma-amino-butyric acid (GABA) neurotransmitter systems have been implicated in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…A three-dimensional affine transformation, similar to that used for spatial normalization in SPM, has been applied successfully to perfusion SPECT images of healthy subjects (34), and SPM has been applied to a BZR SPECT study comparing schizophrenic patients with controls (35). However, given the fact that some of the epileptogenic foci may have consisted of small anatomic lesions in our patient group, there may have been slight inaccuracies with spatial normalization of the SPECT images.…”
Section: Discussionmentioning
confidence: 99%
“…A three-dimensional affine transformation, similar to that used for spatial normalization in SPM, has been applied successfully to perfusion SPECT images of healthy subjects (34), and SPM has been applied to a BZR SPECT study comparing schizophrenic patients with controls (35). However, given the fact that some of the epileptogenic foci may have consisted of small anatomic lesions in our patient group, there may have been slight inaccuracies with spatial normalization of the SPECT images.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT studies with [ 123 I]iomazenil reported no group differences in comparison with control subjects (Abi-Dargham et al, 1999; Ball et al, 1998; Busatto et al, 1997; Verhoeff et al, 1999), as did a PET study with [ 11 C]Ro15-4513 (Asai et al, 2008). One group found that medial frontal cortex binding was positively associated with total symptoms, but negatively associated with outcome measures across the brain after displacement of the ligand following a diazepam infusion (Schroder et al, 1997).…”
Section: 0 In Vivo Measurement Of Gaba and Gabarsmentioning
confidence: 94%
“…One group found that medial frontal cortex binding was positively associated with total symptoms, but negatively associated with outcome measures across the brain after displacement of the ligand following a diazepam infusion (Schroder et al, 1997). While other groups also found symptom correlations with binding (Ball et al, 1998; Busatto et al, 1997), another group failed to replicate these symptom correlations using a quantitative measurement of binding not sensitive to cerebral blood flow (Abi-Dargham et al, 1999). Considering what is now known from the post-mortem findings, these essentially negative findings should not be too surprising.…”
Section: 0 In Vivo Measurement Of Gaba and Gabarsmentioning
confidence: 98%
“…Consistent with these postmortem findings, pairedpulse transcranial magnetic stimulation has revealed reduced cortical inhibition (Daskalakis et al, 2002). However, functional imaging studies using ligands for the benzodiazepine receptor (Abi-Dargham et al, 1999) have failed to show altered GABAR densities, whereas magnetic resonance spectroscopy studies of GABA concentrations have reported mixed results (Kegeles et al, 2012;Yoon et al, 2010). Thus, the functional significance of GABA alterations remains to be elucidated.…”
Section: Introductionmentioning
confidence: 91%